Value evaluation of Lisu Costume in Nujiang based on questionnaire survey / Zhu Yangyang , Faridah Sahari - Zhu, Yangyang; Sahari, Faridah (Universiti Teknologi MARA Cawangan Sarawak, 2022)
The traditional women's costume of the Nujiang Lisu people in China has along history, profound cultural connotations, and strong artistic qualities, making it a precious wealth of Chinese national costume culture. However, the Lisu people in China live in border areas with harsh natural conditions, which have led to a general lag in the economic, social, and cultural development of this ethnic region. The traditional costume of the Lisu people is very rich in value. As ethnic cultural resources, these costume values are of particularly significant in the current process of intangible cultural heritage protection and development in China, and should be scientifically evaluated and utilized. This article uses a questionnaire survey method to conduct the research. According to the 15 values of the Nujiang Lisu costume, the questionnaires were designed accordingly.